2009
DOI: 10.33899/mmed.2009.8843
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism, seasonal variations in admission to hospital, and the association of calf deep vein thrombosiswith pulmonary embolism

Abstract: Objective: To look for the presence or absence of seasonal variation of pulmonary embolism (PE). To analyze the effect of age, sex and the presence or absence of deep vein thrombosis(DVT) and its risk factors on the occurrence of PE. To analyze the ECG changes and the presence or absence of sinus tachycardia in patients with acute PE. Method: One hundred three patients with PE were studied retrospectively, during the years 2002-2007 at the intensive and respiratory care unit and general medical units in Ibn-Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…103 patients with PE diagnosis were studied by Al Hayali et al in Iraq from 2002 to 2007; there was no meaningful seasonal variation in incidence of PE in this study. 14 Lee et al reported no seasonal variations in incidence of VTE in Taiwan. The total of 2774 patients older than 18 years old with VTE diagnosis were included in this study.…”
Section: Seasonal Variation Of Vte According To the Region Of Studymentioning
confidence: 97%
“…103 patients with PE diagnosis were studied by Al Hayali et al in Iraq from 2002 to 2007; there was no meaningful seasonal variation in incidence of PE in this study. 14 Lee et al reported no seasonal variations in incidence of VTE in Taiwan. The total of 2774 patients older than 18 years old with VTE diagnosis were included in this study.…”
Section: Seasonal Variation Of Vte According To the Region Of Studymentioning
confidence: 97%